Rehabilitation approaches for visual disorders post-stroke: A systematic review in neurological physiotherapy - Jovita Jutamulia; Elfira Sutanto; Putu Anindya Agrasidi (Universitas Udayana dan Diaspora Taipei Medical University, 2026)
Introduction: Visual disorders after stroke are common and may substantially impair reading, mobility, spatial orientation, activities of daily living, and quality of life. Although various rehabilitation strategies have been developed, the evidence remains heterogeneous across impairment subtypes and intervention modalities. This systematic review aimed to examine rehabilitation approaches for post-stroke visual disorders, identify the types of interventions used, and summarize findings relevant to neurological physiotherapy practice. Methods: A systematic review was conducted following PRISMA principles. Literature searches were performed in PubMed/MEDLINE, ScienceDirect, ProQuest, and Google Scholar from inception to March 2026. Eligible studies involved patients with stroke presenting with visual disorders, including hemianopia, diplopia, visual neglect, and visual perceptual deficits, and evaluated neurological physiotherapy-based rehabilitation interventions. Due to heterogeneity in interventions, outcome measures, and study designs, the findings were synthesized narratively. Results: A total of 1,022 records were identified, and 15 studies were included in the final review. Most included studies were randomized controlled trials published between 2008 and 2025, with sample sizes ranging from 12 to 158 participants. The most common disorder was homonymous hemianopia, while the main interventions included visual scanning training, visual exploration training, smooth pursuit training, vision restoration training, virtual reality-based rehabilitation, and stimulation-based approaches such as tDCS and TENS. Overall, rehabilitation interventions were generally associated with improvements in functional outcomes, including visual search, reading performance, neglect measures, activities of daily living, and vision-related quality of life. Although some multimodal interventions combining visual training with sensory or electrical stimulation showed promising results, the findings varied across studies and should be interpreted cautiously. Conclusion: Rehabilitation approaches for post-stroke visual disorders may support improvements in functional performance and quality of life; however, the evidence remains heterogeneous across visual impairment subtypes, intervention modalities, and outcome measures. Early identification, accurate phenotyping, and individualized rehabilitation planning may help optimize neurological physiotherapy management, but further well-designed studies are needed to determine the most effective intervention strategies.